Cheerleading spirit - Mullarkey, Lisa (Berkeley Heights, NJ : Enslow Publishers, 2011)
"Readers will learn about the power of positive attitudes, pep rallies, and spirit"--Provided by publisher.
Attitude is everything -- Score with spirit -- Pep it up! -- Pep rallies.
10 - 13 years
Keywords: Cheerleading; Cheerleading; Sports